Urotensin-II: More Than a Mediator for Kidney - Ayşe Balat; Mithat Büyükçelik (International Journal of Nephrology)
Human urotensin-II (hU-II) is one of the most potent vasoconstrictors in mammals. Although both hU-II and its receptor, GPR14, are detected in several tissues, kidney is a major source of U-II in humans. Recent studies suggest that U-II may have a possible autocrine/paracrine functions in kidney and may be an important target molecule in studying renal pathophysiology. It has several effects on tubular transport and probably has active role in renal hemodynamics. Although it is an important peptide in renal physiology, certain diseases, such as hypertension and glomerulonephritis, may alter the expression of U-II. As might be expected, oxidative stress, mediators, and inflammation are like a devil's triangle in kidney diseases, mostly they induce each other. Since there is a complex relationship between U-II and oxidative stress, and other mediators, such as transforming growth factor β1 and angiotensin II, U-II is more than a mediator in glomerular diseases. Although it is an ancient peptide, known for 31 years, it looks like that U-II will continue to give new messages as well as raising more questions as research on it increases. In this paper, we mainly discuss the possible role of U-II on renal physiology and its effect on kidney diseases.